Study Abroad at Home: The Impact of a Multilingual and Multicultural Classroom Experience on Non-Native Medical Students' English Language Skills Development - Timea Németh; Erika Marek; Balázs Sütő; Gabriella Hild (MDPI AG, 2024)
Study Abroad programs yield substantial linguistic advantages in addition to fostering academic and intercultural enrichment. Nevertheless, some students miss these programs due to financial constraints, academic commitments, or insufficient language skills. This paper reports the findings of a qualitative action research study that seeks to evaluate the impact of a multilingual and multicultural class, designed as a quasi-Study Abroad experience, on Hungarian medical students' perceived English linguistic development by the end of the semester. Semi-structured focus group interviews were carried out with 42 Hungarian medical students at the end of the spring and autumn semesters of the 2021-2022 and the 2022-2023 academic years. The outcomes of the focus-group interviews indicated that the students had a positive experience studying in a multilingual and multicultural environment; their willingness to engage in English communication, along with an increase in self-confidence, was apparent, ultimately showcasing improved perceived proficiency in English communication skills by the end of the term. Creating an educational setting abundant in linguistic and cultural diversity and integrating multicultural project-based learning activities within the curriculum to simulate a quasi-Study Abroad experience represent methodological frameworks that could serve as pivotal models for shaping similar courses in the future.